Representations of the foreign and self-representations in language classes: theoretical and methodological approaches - López Bermúdez, Daniel Hernán (Rastros Rostros, 2024)
This article proposes some theoretical references and methodological suggestionson the subject of images of the foreign in language classrooms, or more precisely,on the representations of foreign cultures and about one’s own culture. In orderto do this, a brief examination of the concept of social representations is takenas a starting point, and then it is regarded the applicability of this concept in thefield of language didactics using an approach that advocates a reflexive look atone’s own culture and, at the same time, at foreign cultures: the diversified de-scription. This methodological approach aims to warn of the risks of a univocaland reductive vision on this subject, and to give an active and critical role to boththe student and the teacher in the construction of self-images and images of theforeign. However, it is not a question of offering pre-established formulas but ofpresenting a range of conceptual and practical tools, which can be permanentlyexpanded and adapted, in order to undertake a reflexive process that allows the(self-) representations to emerge, identify their sources and examine them witha relativizing view
Keywords: Keywords: social representations, self-representations, language didactics, diver-sified description, methodology.